Relationship between Literacy and Numeracy for Junior High School Students - Yusida Gloriani; Setiyani Setiyani; Siska Firmasari; Turini Erawati (STAI Hubbulwathan Duri, 2023)
The objective of the study was to examine the reading literacy and numeracy skills of Grade VII Junior High School students. This study employs a quantitative descriptive approach. The participants of this study consisted of 35 pupils. Explore methodologies for gathering research data through the utilisation of tests. The research instrument employed was a standardised assessment sheet designed to measure proficiency in reading literacy and numeracy skills. Both the reading literacy exam and the numeracy ability test encompass three cognitive levels. The employed data analysis technique involves calculating the mean value, conducting a regression test, and determining the coefficient of determination. The study findings indicate that the mean reading proficiency surpasses numeracy, however both remain suboptimal. These figures are demonstrated by the mean score of 60.46 on the reading exam and 33.71 on the numeracy test. There is a favourable association between literacy and numeracy ability, which is somewhat interpreted. The proficiency in reading and writing has a significant impact on one's capacity to perform mathematical calculations, accounting for a substantial proportion of 16.8%. The remaining portion is influenced by several other elements. The findings of this study suggest that teachers should incorporate AKM questions into their teaching practices to help students develop a habit of reading and comprehending questions. It is anticipated that this approach will lead to a substantial improvement in students' literacy and numeracy scores.